Phenotypic changes in the brain of SIV-infected macaques exposed to methamphetamine parallel macrophage activation patterns induced by the common gamma-chain cytokine system - Bortell, Nikki; Morsey, Brenda; Basova, Liana; Fox, Howard S.; Marcondes, Maria Cecilia G. (Frontiers in Microbiology, 2015)
One factor in the development of neuroAIDS is the increase in the migration of pro-inflammatory CD8 T cells across the blood–brain barrier. Typically these cells are involved with keeping the viral load down. However, the persistence of above average numbers of CD8 T cells in the brain, not necessarily specific to viral peptides, is facilitated by the upregulation of IL15 from astrocytes, in the absence of IL2, in the brain environment. Both IL15 and IL2 are common gamma chain (γc) cytokines. Here, using the non-human primate model of neuroAIDS, we have demonstrated that exposure to methamphetamine, a powerful illicit drug that has been associated with HIV exposure and neuroAIDS severity, can cause an increase in molecules of the γc system. Among these molecules, IL15, which is upregulated in astrocytes by methamphetamine, and that induces the proliferation of T cells, may also be involved in driving an inflammatory phenotype in innate immune cells of the brain. Therefore, methamphetamine and IL15 may be critical in the development and aggravation of central nervous system immune-mediated inflammatory pathology in HIV-infected drug abusers.